فعالية الوسائط التعليمية القائمة على الفيديو الكرتونية في تحسين مهارة الكلام لدى طالبات الصف التاسع في معهد دار الأبرار بوني - Nurfitri Sari; Agussalim Beddu Malla; Bisyri Abd Karim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to find out the effectiveness of cartoon video as alearning media to improve maharah al-kalam (Arabic speaking skill) of femalestudents at Pesantren Darul Abrar. This study uses a quantitative approachwith a quasi-experimental design. The sample consists of two groups: theexperimental group that used cartoon videos and the control group that usedtraditional learning methods. Data was collected using speaking tests beforeand after the treatment (pre-test and post-test).The validity test shows thatmost items have an r-count higher than the r-table (0.444) with significance <0.05, so the instrument is valid. One item is below the r-table value but stillhas acceptable significance. The reliability test shows a Cronbach’s Alphavalue of 0.800, which means the instrument is highly reliable.The data isnormally distributed (sig. = 0.200) and homogeneous (sig. = 0.200), so itmeets the basic assumptions for regression analysis. The t-test result showsthat religiosity has a significant effect on positive aggressiveness, which inthis context means speaking confidence, with a coefficient value of 0.371 andsignificance of 0.002. This means cartoon videos are effective as learningmedia to improve maharah al-kalam, especially when connected to Islamicvalues that are already present in the pesantren environment.